Epidermal Growth Factor Receptor Mutation Status and Rad51 Determine the Response of Glioblastoma to Multimodality Therapy with Cetuximab, Temozolomide, and Radiation - Wachsberger, Phyllis R.; Lawrence, Richard Y.; Liu, Yi; Rice, Barbara; Daskalakis, Constantine; Dicker, Adam P. (Frontiers in Oncology, 2013)
Purpose: EGFR amplification and mutation (i.e., EGFRvIII) are found in 40% of primary GBM tumors and are believed to contribute to tumor development and therapeutic resistance. This study was designed to investigate how EGFR mutational status modulates response to multimodality treatment with cetuximab, an anti-EGFR inhibitor, the chemotherapeutic agent, temozolomide (TMZ), and radiation therapy (RT). Methods and Materials:In vitro and in vivo experiments were performed on two isogenic U87 GBM cell lines: one overexpressing wildtype EGFR (U87wtEGFR) and the other overexpressing EGFRvIII (U87EGFRvIII). Results: Xenografts harboring EGFRvIII were more sensitive to TMZ alone and TMZ in combination with RT and/or cetuximab than xenografts expressing wtEGFR. In vitro experiments demonstrated that U87EGFRvIII-expressing tumors appear to harbor defective DNA homologous recombination repair in the form of Rad51 processing. Conclusion: The difference in sensitivity between EGFR-expressing and EGFRvIII-expressing tumors to combined modality treatment may help in the future tailoring of GBM therapy to subsets of patients expressing more or less of the EGFR mutant.